Facility management of gas turbine power plants using 3D laser scanning. Issue 1 (31st December 2022) - Marzouk, Mohamed; El-Bendary, Nasr
ABSTRACT: Industrial projects are extremely complex in terms of designing, engineering, construction, operation and maintenance. These projects involve extremely specialized activities during operation and maintenance phases. Optimizing the operation and maintenance phases for mega-industrial complexes such costs as power plants, petrochemicals, pharmaceuticals, and oil refineries increases the potential cost saving and maximizes the net profit. Plant maintenance comprises thousands of tasks, hundreds of workers, huge amount of equipment and material highly dependent on plant size. This research proposes a procedure for facility management using 3D laser scanning technologies in gas turbine power plants. High Density Point Cloud (HDPC) is obtained from 3D laser scanning of the power plant to facilitate the process of maintenance. HDPC is converted to regions in Recap application and the Autodesk Revit add-in imports the point cloud to Autodesk Revit and populates all the required maintenance data. This research describes the developed Power Plant Operation and Maintenance Tool (PPOMT) platform and its components to synchronize the data of the power plant with the online workspace information. All equipment information, the type of maintenance and the tasks to be carried out are defined for facility management purpose.